REVIEW OF LITERATURE ON THE SPECIFICITY OF GENERAL PATHOMORPHOLOGICAL CHANGES IN SATELLITE STRUCTURES UNDER THE INFLUENCE OF CORONAVIRUS - Rasulov H.A.,; Beknazarov Kh.J.,; Mavlonov U.O. , (Central Asian Journal of Medicine, 2025)
Viral infections observed during pregnancy can have a specific impact on the body, leading to various negative outcomes at different stages of pregnancy. This necessitates an understanding of the pathological processes occurring in the placenta (maternal-placental system). Women suffering from viral infections such as herpes, hepatitis, rubella, and measles experience changes in the placenta, which have been studied in this context. In our study, special attention is given to the morphological changes in the placenta resulting from the coronavirus infection (SARS-CoV-2), which has shocked the entire world. The main morphological changes observed in the placenta during COVID-19 infection are presented.